Pengaruh Budaya Organisasi Opmaz terhadap Perubahan Perilaku pada Santri Kelas 12 Ma Ma'had Al-Zaytun - Zahra Asyidda Najibullah; Muhammad N. Abdurrazaq; Sobirin (Jurnal Syntax Admiration, 2025)
This study aims to: (1) whether or not there is a relationship between OPMAZ organizational culture and behavioral changes in grade 12 students of MA Ma'had Al-Zaytun; (2) the influence of OPMAZ organizational culture on behavior changes in grade 12 MA Ma'had Al-Zaytun students as administrators and non-administrators of the organization. The research method used is a quantitative approach with the theory used in this study being Robbins (1996) theory, namely organizational culture and behavior change theory. A simple linear regression test was used in the study to determine the influence, and the determination coefficient (R2) was used to determine the percentage of influence on the number of samples of 76 respondents and a total population of 579. The results of the study show that: First, there is a positive relationship between OPMAZ organizational culture and changes in student behavior, which is evidenced by the value of the determination coefficient (R²) of 0.485 or 48.5%, which shows that around 48.5% of the variability of student behavior changes can be explained by variations in OPMAZ organizational culture. Second, a simple linear regression test revealed that OPMAZ organizational culture had a significant influence on changes in student behavior, with a regression equation of Y = 0.6964X and then Scatter Plot analysis with the Standardized Coefficients method showed a strong positive linear relationship between the two variables. Based on the results of the analysis, the change in student behavior was categorized into 4 quadrants actually and 2 quadrants based on regression results, which showed the similarity of the level of organizational culture and changes in student behavior from sufficient to good.